EMPLOYEE PERFORMANCE IN AN EFFORT TO IMPROVE QUALITY AND EFFICIENCY IN PPKS MARIHAT - Riska Devi; Imsar Imsar (Jurnal Manajemen, 2023)
The aim and benefit of the research as a result of the internship carried out by the author is so that PPKS Marihat can understand how employee performance can be improved to achieve increased quality and efficiency in PPKS operations. The research method used in this research is qualitative research. The questionnaire used in this research is an open questionnaire where the answers are filled in by employees divided into 10 people so that they get in-depth information. The sample data source used was purposive sampling. The results of this research show that employees who show better performance tend to provide services that are more responsive, accurate and in line with customer needs. High-performing employees also tend to be able to complete tasks more efficiently, reduce turnaround time, and minimize waste of resources.